Musik Dalam-Toko dan Perilaku Pembeli: Kajian Empiris di Minimarket - Tintin Suhaeni; Sri Raharso; Ivon Sandya Sari Putri (Inovbiz: Jurnal Inovasi Bisnis, 2020)
This study experimentally tests the effects of in-store background music on the shopping behavior of its customers. Field experiments employ pre-experiment the one group pretest-posttest. The researcher chooses a kind of musics tempo and volume as structural characteristics (2 x 2 factorial experiment).  The analysis technique used is the analysis of variance (ANOVA).  The results of the analysis found that tempo and volume of music did not play a significant role in the amount of money spent, but influence significantly on shopping time and mood change. The research answered urgency for designing the musical environment in the retail stores to influence shopping experience and consumer responses, especially for a small store (minimarket).